Continuous wave laser probed thermal nonlinearity in TiO2 and TiO2-dye nano colloidal. (October 2021) - Pramodini, S.; Aravinda, L.S.; Nagaraja, K.K.; Poornesh, P.
Highlights: TiO2 nanoparticles with Anatase & Rutile phases are synthesized using sol-gel method. χ (3) of the nano colloidal solutions is studied using z-scan technique. All samples display both absorptive and refractive optical nonlinearity. A better nonlinearity is observed in Anatase TiO2 – dye nano colloidal solution. Abstract: Herein, we report on the nonlinear optical studies on the nano colloidal solutions of titanium dioxide (TiO2 ), TiO2 -dye and acid blue dye in distilled water under continuous wave laser using the z-scan technique. The phase and structural properties of the sol–gel synthesized TiO2 nanoparticles at different temperatures were analyzed by x-ray powder diffraction (XRD) studies. The transmission electron microscopy (TEM) images confirmed that with an increase in calcination temperature, crystallite size increases. Further, the Fourier transform infrared (FTIR) spectra validate the synthesized TiO2 nano particle's structure. The results from the z-scan reveal self-defocusing and reverse saturable absorption (RSA) behaviors of nano colloidal. The real and imaginary parts of third-order nonlinear optical susceptibility χ (3) were determined and estimated as 10 −6 esu. Also, the optical limiting behavior of the samples is studied; a clamping of around ~ 4 mW is observed for the TiO2 -dye nano colloidal.